Pengaruh Air Cucian Beras Terhadap Pertumbuhan Tanaman Cabai (Capsicum Frutescens) - Nurul Aini; Yessita Puspaningrum; Ana Mariatul Khiftiyah; Miftachul Chusnah (AGROSAINTIFIKA, 2023)
Rice washing water is household waste that is often wasted and is no longer used, even though rice washing water still contains nutrients in the form of vitamins A, C, B1, carbohydrates, phosphorus, potassium, magnesium, nitrogen and iron. Vitamin B1 (thiamin) dissolves in water when washing rice. Vitamin B1 contained in the water used to wash rice has a role in metabolism. The nutritional content in rice washing water can be used to support the growth and development of chili plants. In this study, rice washing water was used as liquid fertilizer for chili plants. The research design was a completely randomized design with the holding variable being the concentration of rice washing water (0%, 25%, 50% 75% and 100%) with 3 repetitions each. The data obtained were analyzed using SPSS Anava followed by Duncan's test. The results showed that the concentration of rice washing water at 100% was the treatment that had the best effect on the growth of chili plants (Capsicum frutescens).